Glucose and Calcium Profile in Infants of Diabetic and Nondiabetic mothers- A Comparative Study - Islam, Md Manirul; Ahmmad, Be Nazir; Karim, Md Rezaul; Islam, Md Rokibul; Uddin, Md Belal; Hoque, Md Sanaul (TAJ: Journal of Teachers Association, 2023)
Background: Diabetes is one of the commonest and most important metabolic disorders that affect the health of pregnant women and infants. Diabetic mellitus is one of the most common metabolic disorders complicating pregnancy. The neonatal mortality rate is over five times that of nondiabetic mothers and is higher irrespective of birth weight and gestational age. There has been significant improvement in the outcome of diabetic pregnancies largely due to better metabolic control before and during pregnancy and vigorous neonatal care in developed countries. The management in our country still poses a major challenge. Methods: This case-control study was designed to find out the association between an infant's hypoglycemia and hypocalcemia with maternal diabetes. For the research, a total of 300 neonates were selected, where cases were selected from infants of diabetic mothers, and the control group was selected from infants of nondiabetic mothers. The mothers were interviewed by specific questionnaire, selected neonates were examined, and some biochemical tests were done to find out the outcome. Results: The study included 300 neonates of diabetic and nondiabetic mothers. The mean age of the Mothers of these neonates was 25.36 (SD±5.50) years. Among diabetic mothers 115(76%) had GDM and 36(23.8%) had PGDM. It is revealed that 83 (55%) of 150 mothers took insulin as the treatment. Hypoglycemia in neonates of diabetic and nondiabetic mothers right after birth at their first ½ hour of age 111 (37%). Hypoglycemia was found in 94 (62.3%) of infants of the diabetic mother than only 17(11.4%) in infants of the nondiabetic mother. Where the p-value is <0.001, which explains developing hypoglycemia in the infant of a diabetic mother is higher than nondiabetic mother. The number of hypocalcemic infants of the diabetic mother was 34 (22.5%), while hypocalcemic infants of the nondiabetic mother were only 8 (5.4%), which is significantly (p-value <0.001) lower. Conclusions: Hypoglycemia and hypocalcemia in infants were directly associated with the presence of diabetes during pregnancy. In spite of intensive management of maternal diabetes, the infants of diabetic mothers continue to be a high-risk population. Among the pregnancies complicated by diabetes, GDM continues to have a major contribution. Hypoglycemia remains the most common biochemical abnormality, followed by hypocalcemia. Therefore, this pregnancy complication will require increased re- sources to manage appropriate glycemic control during pregnancy and reduce adverse perinatal outcomes. TAJ 2022; 35: No-2: 93-102